Mechanical work and physiological responses to simulated flat water slalom kayaking - Macdermid, P. W.; Osborne, A.; Stannard, S. R. (Frontiers in Physiology, 2019)
The purpose of this study was to assess the physical work demand in relation to metrics of force and subsequent physiological response to a simulated flatwater slalom competition. Eight New Zealand team members completed a standard incremental step-test to ascertain power:oxygen consumption relationship. This was followed by a simulated race run where breath-by-breath analysis along with force and power data logged at 50 Hz to determine stroke length, impulse, peak force, time to peak force, and rate of peak force per stroke. Physiological response to negotiating a flatwater slalom course was greater than straight-line paddling (36.89 ± 2.01 vs. 32.17 ± 1.97 ml·kg-1·min-1, p = 0.0065) at the same power output. Mean power output for the duration of the simulated race (91.63 ± 7.19 s) was 203.8 ± 45.0 W, incurring an oxygen deficit of 1.386 ± 0.541 L·min-1 translating to an overall anaerobic contribution of 32 ± 18% and aerobic contribution of 68 ± 18%. Moderate to strong relationships between time duration and stroke peak force (R2 = 0.354, R2 = 0.485) and rate of peak force development (R2 = 0.345, R2 = 0.426) but not for stroke length (R2 = 0.022, R2 = 0.012), impulse (R2 = 0.088, R2 = 0.097) or time to peak force (R2 = 0.001, R2 = 0.0001) for left and right strokes, respectively. The number of propulsive (<0.6 s) strokes outweighed turning/driving (>0.6 s) strokes with a ratio of 94:6%. Longer stroke duration was significantly correlated to greater impulse (R2 = 0.507, p < 0.0001) and time to peak force (R2 = 0.851, p < 0.0001), but a lower rate of force development (R2 = 0.107, p < 0.0001). The results show that a flatwater slalom under simulated race conditions entails initial supra-maximal (anaerobic) work rate with a subsequent transition to one associated with maximal aerobic capacity. Inability to sustain work done and the subsequent decline in peak force and force profile per stroke requires further research regarding strategies to enhance performance.